2021
DOI: 10.1021/acs.jpclett.1c02729
|View full text |Cite
|
Sign up to set email alerts
|

Energetics, Interlayer Molecular Structures, and Hydration Mechanisms of Dimethyl Sulfoxide (DMSO)–Kaolinite Nanoclay Guest–Host Interactions

Abstract: Two-dimensional (2D) kaolinite nanoclay is an important natural mineral with promising application potential, especially tuned with organic intercalates. However, thus far, the organics–kaolinite guest–host interactions, the atomic scale structures of organic intercalates under confinement, and molecular level mechanisms of hydration are rarely systematically explored using both experimental and computational methodologies. We integrated density functional theory with dispersion scheme (DFT-D) with various exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…These FTIR results indicated that the phosphoryl group and −COOH groups of LPS had a strong interaction with the surfaces of E-Kaol 30 , and especially, the phosphoryl group may have been seriously damaged and reduced. This result is similar to the cell membrane damage of E. coli by dissolved Al from the Colombian Amazon clay as reported by Londono et al [15] After the interaction with E. coli, the IR absorption at 3684 cm −1 from the inner surface hydroxyl groups [42] of E-Kaol 30 blueshifted to 3689 cm −1 . The bands at 452 and 521 cm −1 that were SiO deformation [42] of E-Kaol 30, also showed a blueshift.…”
Section: Interfacial Interaction Between Om and Edge Surfaces Of Kaolsupporting
confidence: 89%
See 1 more Smart Citation
“…These FTIR results indicated that the phosphoryl group and −COOH groups of LPS had a strong interaction with the surfaces of E-Kaol 30 , and especially, the phosphoryl group may have been seriously damaged and reduced. This result is similar to the cell membrane damage of E. coli by dissolved Al from the Colombian Amazon clay as reported by Londono et al [15] After the interaction with E. coli, the IR absorption at 3684 cm −1 from the inner surface hydroxyl groups [42] of E-Kaol 30 blueshifted to 3689 cm −1 . The bands at 452 and 521 cm −1 that were SiO deformation [42] of E-Kaol 30, also showed a blueshift.…”
Section: Interfacial Interaction Between Om and Edge Surfaces Of Kaolsupporting
confidence: 89%
“…[ 15 ] After the interaction with E. coli , the IR absorption at 3684 cm −1 from the inner surface hydroxyl groups [ 42 ] of E‐Kaol 30 blueshifted to 3689 cm −1 . The bands at 452 and 521 cm −1 that were SiO deformation [ 42 ] of E‐Kaol 30, also showed a blueshift. Notably, the XPS results confirmed the reduction of P content as assumed by FTIR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, nanoconfined water has always received intensive attention since it plays a significant role in many applications such as drug delivery, DNA sequencing and therapeutic, , nanofluidic, water purification, , and energy storage in supercapacitors and batteries. , Compared to the bulk water, nanoconfinement with different shapes and dimensions can lead to anomalous changes in the structures, dynamics, and other physical properties of water, such as distinct ice phase, , enhancement of the diffusion rate and different modes of diffusion, and the transformation of the hydrogen bond (HB) network. ,, In spite of great progress in experimental characterizations, it still has to fight against enormous challenges for experimental observations to provide a comprehensive understanding of the unique properties of nanoconfined water. , As a powerful complementary analysis tool, theoretical simulations, especially molecular dynamics (MD), can offer a molecular-level insight into the structures and dynamics of water confined in multi-dimensional nanoscale environment. …”
Section: Introductionmentioning
confidence: 99%
“…1,15−17 Nanoclays, with nanometer-scale layering, are inorganic products that have been collected from stones and used as medical formulations for thousands of years. 18 They have unique morphologies, good biocompatibility, abundant surface hydroxyl groups, 19−22 and high guest loading capacity, 23,24 which have been developed to deliver various therapeutic agents (such as chemodrugs, enzymes, antibacterial agents, and polymer self-healing agents). 18,25 In particular, DOX has been efficiently loaded into nanoclays to enhance anticancer efficacy.…”
mentioning
confidence: 99%
“…Nanoclays, with nanometer-scale layering, are inorganic products that have been collected from stones and used as medical formulations for thousands of years . They have unique morphologies, good biocompatibility, abundant surface hydroxyl groups, and high guest loading capacity, , which have been developed to deliver various therapeutic agents (such as chemodrugs, enzymes, antibacterial agents, and polymer self-healing agents). , In particular, DOX has been efficiently loaded into nanoclays to enhance anticancer efficacy. However, their mechanisms of DOX delivery remain unclear, and the modified polymers on nanoclays may induce a synergistic drug-loading effect, so it is necessary to investigate in vitro binding and release mechanisms of DOX from unmodified nanoclays.…”
mentioning
confidence: 99%